The experiences of people living with HIV/AIDS and of their direct informal caregivers in a resource-poor setting - Majumdar, Basanti (The International AIDS Society, 2010)
BACKGROUND: HIV/AIDS is a critical concern in South Africa, where extreme poverty and gender issues are major determinants of health. A comprehensive home-based care programme is needed to lessen the burden placed on the caregivers of those suffering from HIV/AIDS. The purpose of this study was to explore and describe the challenges faced by people who are living with HIV/AIDS and by their caregivers in resource-poor, remote South African villages. METHODS: In-depth interviews were conducted with nine persons living with HIV/AIDS and their nine direct informal caregivers. Interviews explored the themes of physical, emotional and social wellbeing. Two focus groups, one involving community leaders and one with local health care providers, were conducted to build on themes emerging from the in-depth interviews. A thematic analysis of the transcripts was performed. RESULTS: This study sheds light on the needs of persons living with HIV/AIDS and the needs of their direct informal caregivers in a rural area of the Eastern Cape province of South Africa. These needs include: physical/medical, social, material, financial, physiological/emotional, gender issues, and instrumental. CONCLUSIONS: In developing home-based care programmes, it is vital to consider the perceived needs of persons living with HIV/AIDS and their direct informal caregivers. The results from this study serve as a basis for the development of a home-based care programme in one resource-poor setting of South Africa and could provide a model for such programmes in similar areas.